Endosperm formation in aposporous Crataegus (Rosaceae, Spiraeoideae, tribe Pyreae) parallels to Ranunculaceae and Poaceae - Talent, Nadia (The New phytologist, 2007)
Apomixis in Crataegus is primarily aposporous and requires pollination. The embryo sac is of the Polygonum type. A combination of meiotically unreduced embryo sacs with apparently reduced pollen would violate the usual requirement for a 2 : 1 ratio of maternal to paternal contributions to the endosperm. We therefore investigated the origin of endosperm in seeds of sexual diploids and apomictic polyploids of the sister genera Crataegus and Mespilus. Flow-cytometric DNA measurements from embryo and endosperm in mature seeds were converted to ploidy levels using leaf-tissue information. The diploids had triploid endosperm. In c. 60% of seed from polyploids, one sperm apparently contributes to the endosperm, while 25% or more may involve two sperm. Additional results suggest that trinucleate central cells also occur. Fertilization of meiotically unreduced eggs is indicated. The ratio of maternal to paternal contributions to the endosperm in these apomictic Crataegus is not constrained to 2 : 1. They thus resemble some Sorbus (Pyreae) and very distantly related Ranunculus (Ranunculaceae). It is suggested that Paspalum (Poaceae) may have similarly flexible endosperm ploidy levels